International Economic Policies in a Globalized World - Katayama, Seiichi; Ursprung, Heinrich W. (Springer Berlin Heidelberg, 2004)
In this volume we collected some of the papers that were presented at the RIEB (The Research Institute for Economics and Business Administration) International Conference at Kobe University on March 25 and 26, 2000. The contributions invited for presentation all dealt with specific aspects of the conference topic "Trade Policy: Political Economy and Dynamic Issues". In the meantime the papers collected in this volume have been revised, and some of them have been published in professional journals. This volume thus contains published as well as hitherto unpublished contributions. We are grateful to all the authors and the conference participants, espe cially to those who cheerfully served as discussants and chairpersons. Our thanks also go to our colleagues at the RIEB for their encouragement, and especially to the RIEB's Director, Professor Shoji Nishijima for his support of the project. We are also grateful to Professor Arye Hillman at Bar-Han University, who kindly read parts of the manuscript and supplied useful com ments and suggestions. In the editorial process we were fortunate to be able to rely on an excellent and able team: we are extremely grateful to Minako Okuno, Yuji Fujinaka, Tetsuya Saito for their outstanding work and to Shinya Horie who undertook the pains taking job and completed the camera-ready copy for publication. We are also grateful to Professor Charles Noussair of Emory University who kindly supplied suggestions